Efficacy of Percutenous Trigger Finger Release - Ali, Muhammad Qasim; Sheikh, Saeed Ahmed; Sahito, Badaruddin; Arif, Muhammad; Jamali, AR (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the efficacy of trigger finger release with the percutaneous technique.Study Design: Cross-sectional study.Place and Duration of Study: Department of Orthopedic Surgery, Jinnah Post Graduate Medical Center, Karachi Pakistan, from Mar 2017 to Mar 2018.Methodology: One hundred and three patients were selected through the outpatient department after they meet the inclusion criteria with one or more trigger fingers in whom percutaneous release was indicated. Patients with previously open release, carpel tunnel syndrome, osteoarthritis of the hand and Dupuytren's contracture were excluded.Results: The mean age of patients was 34.79 ± 14.08 years with a range of 17-62 years. More patients were male (56.3%), and females were 43.7% with a male to female ratio of 1.27:1. Accordingly, 95 (92.2%) out of 103 had complete relief of symptoms and the procedure was thus efficacious in these patients. Among the remaining 7.8% of patients in whom it was not efficacious, about 2.2% had partial relief while 5.6% had either no benefit or worsening of symptoms as assessed on the 8th week post-operatively. Age was a significant effect modifier (p